2020
DOI: 10.26444/aaem/116574
|View full text |Cite
|
Sign up to set email alerts
|

Does place of residence affect patient satisfaction with hospital health care?

Abstract: Introduction and objective.Measuring the level of patient satisfaction is a useful tool in delivering quality care that is responsive to consumer preferences. Various socio-demographic factors might be considered as potential predictors of patient satisfaction. The aim of the study was to assess whether place of residence (rural/urban) affects patient satisfaction with hospital health care. Materials and method. Data were obtained using face-to-face questionnaire, administered in five large, urban hospitals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The finding of this study is similar to some studies that reported that lower education level was greater satisfaction with health care service (20,21) and also is consistent with a study that reported a higher level of education was less satisfied with health care (22) .This can occur because patients with high educational levels possess more information about treatment alternatives and expect higher care standards and therefore are more critical in this regard.In regression analysis, significant associations between place of residence and patient satisfaction were identified, respondents in the rural area remained significantlyassociated with respect to satisfaction with hospital services the coefficient 0.63, p=0.05. The result of this study is in line with the study (23) . This may be due to that some of the rural places they…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study is similar to some studies that reported that lower education level was greater satisfaction with health care service (20,21) and also is consistent with a study that reported a higher level of education was less satisfied with health care (22) .This can occur because patients with high educational levels possess more information about treatment alternatives and expect higher care standards and therefore are more critical in this regard.In regression analysis, significant associations between place of residence and patient satisfaction were identified, respondents in the rural area remained significantlyassociated with respect to satisfaction with hospital services the coefficient 0.63, p=0.05. The result of this study is in line with the study (23) . This may be due to that some of the rural places they…”
Section: Discussionsupporting
confidence: 92%
“…Information obtained in other studies also found that education was one of the decisive factors influencing the completeness of ANC (Ba et al, 2019;Jafaralilou et al, 2019;Teye-Kwadjo, 2019). The level of education a person has a role in one's perception of the quality of services available or received (Maślach et al, 2020;Hijazi et al, 2018).…”
Section: Resultsmentioning
confidence: 84%
“…Research on the relationship between population density and treatment satisfaction show inconsistent results. Few studies showed a higher overall satisfaction among rural residents [ 42 , 43 ], whereas the majority of studies reported no [ 44 , 45 ] or varying differences between rural and urban populations in treatment satisfaction [ 46 48 ]. Thus, research assigns solely a minor role to geographical characteristics in explaining treatment satisfaction [ 48 ].…”
Section: Discussionmentioning
confidence: 99%